Do I care: How does the provision of information about the environmental benefits of grain legume cultivation in Sweden influence consumers? - Köster, Kalle Nils Valentin (SLU/Dept. of Biosystems and Technology (from 130101), 2022)
Grain legume cultivation is promoted to be beneficial for Swedish agriculture due to grain legumes´ ability to engage in biological nitrogen fixation, function as break-crops in cereal-based cropping systems and a general increase in biodiversity. Furthermore, grain legumes are an important pillar of more sustainable diets. Yet, cultivation remains relatively low and consumption levels are below suggested thresholds for achieving sustainable diets: the current daily consumption is 12 grams per person while research suggests that it should reach 50 grams. To achieve this increase means tackling barriers that hinder Swedish farmers from growing more grain legumes and consumers to consume more grain legumes. This study aims to explore how providing information on environmental benefits from grain legume consumption influences consumers’ Willingness-to-pay for Swedish produced yellow peas. In this, individual differences are measured through the Environmental Schwartz Values Survey. It is further accounted for differences in products by including conventional, organic and small-scale organic resellers of Swedish yellow peas. In this, descriptions of operations and goals of the companies were provided to participants. An online survey with 329 participants showed that providing information on environmental benefits did not affect participants’ Willingness-to-pay. This result was independent of participants’ endorsement of biospheric values as well as the product type. However, participants were willing to pay a significantly higher price for small-scale organic yellow peas compared to conventional or organic yellow peas. Still, this increased Willingness-to-pay was limited and showed that participants were not willing to pay the real shelf price of the product. Furthermore, endorsement of biospheric values only correlated weakly with participants’ Willingness-to-pay. One of the most mentioned barriers to increasing the consumption of grain legumes was the lack of recipes. The results of the study suggest that providing information about environmental benefits resulting from the cultivation of grain legumes does not influence participants´ WTP. Future research could focus on the relation between information provision about environmental benefits and intentions to consume grain legumes in the future. Furthermore, it has not been controlled for the effect of the information provided on the operations and goals of the different companies which could have influenced participants´ indication of WTP.